Wprowadzenie rachunku kosztów działań w przedsiębiorstwach komunikacji samochodowej – wyniki badań - Konstantyn, Krzysztof (Conception of introduction of activity based costing in enterprises of car transports – results of research, 2008)
Nowadays we need the more exact analysis of indirect costs than the traditional one that concentrated mainly on direct costs of a company. The paper presents research results that prove the importance of activity based costing for enterprises of car transport.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 181-191